Pengelolaan Wilayah Pesisir Dan Pulau-Pulau Terhadap Masalah Tata Ruang Kota Ambon - Djuna, Kartika; Tjiptabudy, J; Lekipiouw, S Halmes (Jurnal Saniri, 2022)
The construction of the Siloam Hospital by reclaming a small liver area which is a geological protected area has an impact on damage to mangrove areas and sedimentation, thus making several areas in the Lateri area as well as Passo in Baguala District frequent tidal floods during high tide. Mangrove forests in areas in Ambon City are now critical. In the Ambon City Regional Regulation No. 24 of 2012 concerning the Ambon City Regional Spatial Plan (RTRW) in 2011-2031, does not allow reclamation in the Hative Kecil Beach area. invitation and legal consequences of spatial management in Ambon City. The method used is a normative legal research method. The results and discussion show that the Layout in Ambon City is in accordance with the laws and regulations. As regulated in regional regulation Number 24 of 2014 concerning the Regional Spatial Plan (RTRW) of Ambon City from 2011 to 2031, it is in line with Law Number 26 of 2007 concerning Spatial Planning. The RTRW of Ambon City has contained substances including the determination of spatial zones with controlling space utilization carried out by licensing, giving intensive and disincentives as well as the introduction of sanctions and spatial planning in Ambon city that is not in accordance with the Ambon City RTRW. Based on the assessment of the Regional Development Planning Agency (Bappeda) in 2017 that there was a space utilization deviation of 47.5%. The legal consequence is that the form of licensing that is not in accordance with the regional spatial plan is canceled by the government in accordance with its authority.